2007
DOI: 10.7205/milmed.172.5.520
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude of Infantry Soldiers to Hearing Conservation

Abstract: An effective Army hearing conservation program should be comprehensive. It should incorporate appropriate knowledge, sociological issues, and economic considerations such as choice making and opportunity cost. There should be a well-structured hearing education program with targeted and appropriate behavioral modification. It should be compulsory and include lectures and videos given at least once a year. Improvements are required to increase the proper use of personal hearing protection devices and thus reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…Typically, hearing loss is worse in the ear on the side opposite the shoulder that supports the fi rearm. Another explanation suggested by Okpala ( 21 ) is that Infantry Soldiers often leave the left ear unprotected to aid communication. Armored Soldiers and Combat Engineers had not perceived a change in their hearing.…”
Section: Discussionmentioning
confidence: 97%
“…Typically, hearing loss is worse in the ear on the side opposite the shoulder that supports the fi rearm. Another explanation suggested by Okpala ( 21 ) is that Infantry Soldiers often leave the left ear unprotected to aid communication. Armored Soldiers and Combat Engineers had not perceived a change in their hearing.…”
Section: Discussionmentioning
confidence: 97%
“…[20] The education regarding risk factors for hearing loss was estimated as adequate by 80% participants of this study, and 95% of them reported that they had adequate knowledge about risk areas around weapons and the use of HPDs. In a British study [8] inadequate education of the HCPs was reported, and all the infantry soldiers in this study had experienced temporary hearing loss. Moreover, communication difficulty was the most acknowledged problem.…”
Section: Exposure To Noisementioning
confidence: 69%
“…The compliance of an HCP is dependent on knowledge and attitude among the conscripts. [8] All conscripts are educated in the risks and consequences of NIHL, levels of noise exposure from weapons and vehicles and how to protect themselves in accordance with the Safety Regulations. The soldiers used earmuffs, helmets with earmuffs, or a combination of earplugs and earmuffs.…”
Section: Introductionmentioning
confidence: 99%
“…As in the above quoted survey, the participants in our study too found use of hearing protection devices to be incompatible with other gear, uncomfortable and an impediment to hearing and communication. 7 Other military studies have found that acoustic trauma in conscripts could be prevented with suitable, well-fitted protection devices and proper safety measures while planning training schedules. 8,9 However in the present study our survey revealed low levels of awareness towards hearing protection devices.…”
Section: Discussionmentioning
confidence: 99%
“…These included communication difficulties, discomfort, and the impracticability of using them in certain circumstances. 7 In our study, the KAP survey established that most cadets were unaware of the long-term consequences of ENT morbidity and its effect on service, hearing protection devices or hearing conservation. Due to the disciplined and structured training schedule, noise exposure due to leisure time activities was minimal.…”
Section: Discussionmentioning
confidence: 99%